PROBLEMATIKA CAKUPAN WILAYAH INDIKASI GEOGRAFIS PISANG TONGKA LANGIT AMBON: The Area Coverage Issues in Geographical Indications Pisang Tongka Langit Ambon - Wardani, Aulia Tri; Nugrahani, Rr. Aline Gratika (Faculty of Law, Universitas Trisakti, 2025)
Indonesia is a tropical country that is rich in natural resources and has a very diverse biological and animal diversity from various regions. Each region in Indonesia has processed products that contribute to the distinctive characteristics of each region which can certainly improve the economic value in the region. Legal protection is needed to guarantee the authenticity of the origin of a product produced. This is what gives rise to a geographical indication. A product that aspires to be designated a geographical indication must possess a certain degree of uniqueness or distinctive characteristics. One illustrative example of a geographical indication product is the Pisang Tongka Langit, an endemic variety native to Eastern Indonesia, particularly the Maluku and Papua regions. The city of Ambon is one of the principal locations where this banana is processed. In order for a product to be designated as a geographical indication, it is necessary to have a certain sign that demonstrates the origin of the product from a specific area or region and possesses distinctive features or characteristics that differentiate it from other regions. Therefore, it is necessary to know the standard coverage area that can be used for naming a geographical indication product.